Pharmacogenomic biomarkers in drug labels: what do they tell us?. (February 2014) - Tutton, Richard
Aim: This article investigates the number of drugs on the market with pharmacogenomics (PGx) biomarker data in their labels using two public sources – the US FDA and the PharmGKB.Methods: The article analyzes the FDA Table of Pharmacogenomic Biomarkers in Drug Labels to show the number of drugs with PGx biomarker information in their labels. Scrutinizing the language of labels, it also engages with whether this information is intended to direct clinicians to take particular actions or not, and whether biomarker information is included on grounds of drug efficacy or to improve safety. The FDA table is compared to the PharmGKB Drug Labels with PGx info database to highlight how they differ in the number of drugs that they include.Conclusion: Analysis of the FDA and the PharmGKB data show that approximately 12% of drugs licensed in the period 1998–2012 had PGx biomarker information included in their labels at the time of their approval. Of that number, labels direct clinicians to utilize PGx testing prior to prescribing treatments in only 14 cases. This clearly falls short of expectations many had in the 1990s about the transformative impact of PGx. In most cases, the inclusion of this information currently has limited or no direct clinical utility. Original submitted 23 July 2013; Revision submitted 30 September 2013